Amalan rangka kepimpinan pengetua serta hubung kaitnya dengan komitmen guru di dua buah sekolah menengah kluster kecemerlangan di daerah Muar - Idris, Mastura (2013)
This descriptive survey study was conducted in order to examine the framework leadership practice of Principals Secondry Cluster Schools in Muar and how it effects teacher’s commitment level. The study involved a sample of 75 teachers in Secondry Cluster School in Muar. The questionnaires consist of three sections with the aim of obtaining background information, leadership framework and teachers commitment level. The study instrument was tested on 20 teachers from one of the ‘Sekolah Berprestasi Tinggi’ in Muar. The study showed a high item reliability, 0.873 for principal’s leadership framework and 0.905 for motivation. The research data was analyzed using SPSS version 17.0 to obtain the mean, standard deviation, percentage and spearman rho correlation. The research finding indicated that the main leadership practice was the structural framework and the teacher’s commitment level is high. The analysis showed a significant relationship between resource, symbolic, politic and structural leadership framework and teacher’s commitment level. Finally, a few suggestions have been made for futher research in future